Assessing the effects of silver nanoparticles on monolayers of differentiated Caco-2 cells, as a model of intestinal barrier. (June 2018) - Vila, Laura; García-Rodríguez, Alba; Cortés, Constanza; Marcos, Ricard; Hernández, Alba
Abstract: Since ingestion is one of the main routes of entry of nanoparticles (NPs) in our organism, simple and fast in vitro models of the intestinal barrier can be helpful to evaluate NPs risk. The human colon adenocarcinoma Caco-2 cell line has been extensively used due to its ability to differentiate, forming a well-structured cell monolayer. In this study, we have used these differentiated cells as a model of intestinal barrier to evaluate a wide set of effects caused by exposure to silver nanoparticles (AgNPs) with an average size of 7.74 nm. Different parameters such as toxicity, monolayer integrity and permeability (assessed by changes in cells' morphology and gene expression pattern), internalization (uptake), translocation, and induction of DNA damage (DNA breaks and oxidative DNA damage) were evaluated. No significant effects were observed on the monolayer's integrity/permeability after exposure to silver nanoparticles, although cellular uptake was demonstrated by using confocal microscopy. Despite the observed uptake, no translocation of AgNPs to the basolateral chamber was demonstrated with any of the different experimental approaches used. The genotoxic effects evaluated using the comet assay indicate that, although AgNPs were not able to induce direct DNA breaks, its exposure induced a significant increase in the oxidative DNA damage levels, at non-toxic concentrations. Highlights: An in vitro model of intestinal barrier constituted by differentiated Caco-2 cells has been used. AgNPs uptake depends on the differentiation state. No morphological/functional changes in the barrier were observed. Confocal microscopy detects uptake, but nor translocation. Exposed cells present increased levels of oxidized damage in DNA.